Method for phenotypic identification of Acinetobacter seifertii bacteria - E. P. Sivolodskii; L. A. Kraeva; E. V. Melnikova (Инфекция и иммунитет)
Abstract. The aim of the study is to increase the accuracy of Acinetobacter seifertii species identification by the phenotypic method. Study objects: 5 strains of A. seifertii (3 isolated in the microbiological laboratory at the Military Medical Academy, 2 strains obtained from the Pasteur Institute (St. Petersburg)). Clinical strains of the A. baumannii group (Ab group) isolated at the Military Medical Academy in 2023–2024 were also studied: A. baumannii (n = 152), of which 37 strains of the tryptophandestruens biovar, A. nosocomialis (n = 12), A. pittii (n = 6), 3 strains of A. calcoaceticus from the Neva River. The type of such strains was determined by MALDI-ToF mass spectrometry. The belonging of the strains to the Ab group was established by taxonomic tests. The biovar A. baumannii bv. tryptophandestruens was determined by a chromogenic reaction on sodium benzoate-containing nutrient medium. Urease of rapid activity was detected by a micro-volumetric method assessed 3 hours later. Utilization of D-xylose as the only carbon source was determined on a nutrient medium containing (g/l): D-xylose 2.0; NH4CI 5.0; NH4NO3 1.0; Na2SO4 2.0; K2HPO4 3.0; KH2PO4 1.0; MgSO4 0.1; bromothymol blue 1.6% aqueous solution 4 ml; bacteriological agar 15.0; distilled water 1 L; pH 7.2±0.2; sterilization at 112°C 20 min. A pure bacterial culture was studied, in which signs of the Ab group and growth on a sodium acetate-containing nutrient medium were previously detected (control of no auxotrophy). The agar bacteria culture was suspended in 0.1 ml of 0.85% sodium chloride solution, one loop of bacterial suspension was sown with a stroke on a nutrient medium with D-xylose and a medium without D-xylose (control), incubated aerobically at 30°C 24–48 hours. The absence of bacterial growth on a medium with D-xylose and a medium without D-xylose in the presence of their growth on a nutrient medium with sodium acetate indicates belonging to the species A. seifertii. Studies showed that all A. seifertii strains do not utilize D-xylose, and all strains of other species of the Ab group utilize D-xylose. A. seifertii bacteria do not utilize L-arabinose, however, 29.6±3.7% of A. baumannii strains do not utilize L-arabinose, including all 37 strains of the tryptophandestruens biovar, which determines the unreliability of this test for the identification of A. seifertii. Most strains of A. seifertii (4 out of 5) have a urease of rapid activity, which suggests their proximity to the species A. nosocomialis. A method has been developed for identification of A. seifertii bacteria based on a set of phenotypic features of Ab group bacteria with a test for D-xylose utilization. It has been established that the use of the D-xylose utilization test in conjunction with the detection of rapid urease activity allows to accurately identify the bacteria A. seifertii and A. nosocomialis among other species of the Ab group.